Musa paradisiaca L. and Musa sapientum L. : A Phytochemical and Pharmacological Review - Mohammad Zafar Imam, Saleha Akter (Journal of Applied Pharmaceutical Science)
Musa paradisiaca L. and Musa sapientum L. (Musaceae) are mainly grown in the tropical and subtropical countries and are widely used for its nutritional values all over the world. The fruits as well as the other parts of the plant are used to treat different diseases in human in traditional medicine. This review presents the scientific information on the traditional uses, phytochemistry and pharmacology of these two species. Both M. paradisiaca and M. sapientum are traditionally used in diarrhoea, dysentery, intestinal lesions in ulcerative colitis, diabetes, sprue, uremia, nephritis, gout, hypertension and cardiac disease. This review reports the phytochemicals isolated and identified from fruit pulp, peel, seeds and flowers. A comprehensive assessment of the biological activities of different extracts is included and possible mechanisms and phytochemicals involved have been correlated.
Keywords: Musa paradisiaca, Musa sapientum, Musaceae, Traditional medicine, Phytochemicals, Pharmacological activities